AN EXPERIMENTAL STUDY OF MASS TRANSFER OF PLATINUM-GROUP ELEMENTS, GOLD, NICKEL AND COPPER IN SULFUR-DOMINATED VAPOR AT MAGMATIC TEMPERATURES - Peregoedova A.; Baker D.R.; Barnes S.-J. (My University, 2006)
We report results of an experimental study on platinum-group elements (PGE) and Au mass transfer by an S-vapor in the Fe-Ni-Cu sulfide system at magmatic temperatures. Using the tube-in-tube technique, we have examined the quantity of PGE, Au and base-metals (BM) transferred via the vapor from the PGE donor [S-rich (Fe,Ni,Cu)1-x S doped with about 2000 ppm of each PGE and Au] to a S-poor PGE-free pyrrhotite (Po) used as the PGE receiver. At the end of the experiments, the receiver Po contained significant quantities of Ni, Cu, Au, Pt and Pd, but little Ir, Ru and Rh. The most important factors influencing the vapor mobility of Ni, Cu, Au and PGE are the phase assemblage present in the donor, which in turn is controlled by temperature, S, Ni and Cu content of the system, and the sulfur fugacity (fS2). In experiments containing only Au-alloy and monosulfide solid-solution (Mss) in the donor, Cu is transferred more than Ni. Gold is transferred 10 times more efficiently than Pd and Pt, and Pd and Pt are transferred 10 times more efficiently than Rh, Ru and Ir. At the lowest S contents, when Pt-alloys form in the donor system, Pt is transferred less than Pd. In experiments containing Mss and sulfide liquid, the amount of all PGE transferred is higher, although the order remains the same Pd-Pt > Rh-Ru-Ir. The amount of Ni transferred is higher than in the Mss-alloy system. In contrast, the amount of Au transferred is lower where the sulfide liquid is present. The amount of S in the receiver Po may be used as a proxy for fS2. Within each phase assemblage the amount of Ni and PGE transferred increases with the amount of S in the receiver Po suggesting that these elements are transferred as sulfide complexes. In contrast, Cu and Au show no correlation with fS2 suggesting that these elements are transferred as metals. These results are not directly applicable to natural systems because the simplicity of the experiments. Nevertheless three geological systems where these results could be relevant are be considered. Firstly, in the case of PGE deposits some are enriched in Pd, Cu and Au, while some are rich in Pt. According to our experiments this could occur if a magmatic sulfide underwent S devolatilization to form S-poor Mss plus Pt-alloy (to form the Pt-rich deposits) and the vapor transported Cu, Au and Pd to a lower pressure and temperature site and deposited these metals there to form the Pd-rich deposits. Secondly, in the case of magmatic Ni-Cu sulfide deposits, which in many cases are enriched in Cu and Pd; S, Cu and Pd could be transferred from the country rock as a vapor leaving Mss and Pt-alloy in the country rock. Finally, during S devolatilization of mantle nodules, Pd, Cu and Au could be removed by the vapor. © 2006 Elsevier B.V. All rights reserved.
Keywords: COPPER; GOLD; MASS TRANSFER; MONOSULFIDE SOLID SOLUTION; NICKEL; PD DEPOSITS; PLATINUM-GROUP ELEMENTS; PT-ALLOY; S-VAPOR